ANALISIS PEMBELAJARAN DARING MELALUI MEDIA WHATSAPP TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS IV - Yuliarti, Diana Yuliarti; Trisniawati, Trisniawati; Titi Muanifah, Mahmudah Titi Muanifah (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to describe the implementation of online mathematics learning through WhatsApp media and interest in learning mathematics through WhatsApp media students in the fourth-grade Elementary school 2 Lubuk Seberuk. This research uses a quantitative descriptive approach (descriptive research). This study was conducted in Elementary school 2 Lubuk Seberuk, which is located at Lubuk Seberuk, Lempuing Jaya, Ogan Komering Ilir, South Sumatra. The data source of this research is the headmaster, fourth-grade teacher, and all students in the fourth-grade Elementary school 2 Lubuk Seberuk. Data collecting techniques used are observation, interviews, questionnaires, and documentation. The validity of the items was tested using product-moment correlation, while reliability using the formula of Spearman-Brown. The results of the calculation of the reliability of the declared reliable and validation testing experts declared eligible. Data analysis techniques, using quantitative analysis and descriptive. The results showed that (1) the Percentage of the implementation of learning mathematics through the media of WhatsApp on students in the fourth grade of 65,62% with a very high category. Implementation of mathematics learning in online media through WhatsApp using three features some feature to send images, send video, and voice messages. Of the three features, the feature sends the image that is often used because it is easily accessible by all students. Some of the obstacles experienced by students were not able to follow the learning of mathematics through the media of Whatsapp due to the limitations of the quota or having no own mobile phone. To keep students can follow the learning of mathematics so that students can follow the activities offline (outside the network) or around (itinerant teacher). (2) the Percentage of interest in learning mathematics through the media of WhatsApp on students in the fourth grade of 68,75% with a high category. But it turns out not to affect the results of student learning on the assessment at the end of the semester. This is because the learning interest of students in mathematics through the media of WhatsApp is leading to feelings of pleasure, engagement, and ease of students in accessing the media WhatsApp. Whereas the material presented is often in the form of images/photos that may not be understood by the students. As a result, when the final assessment of the odd semester is conducted face-to-face with the protocol of health, the learning outcomes of students the average is still below the KKM.